Exploring the role of the CEO in innovation in life science R&D firms - Rosier, Jan (Cranfield University, 2013)
In order for firms to remain competitive CEOs acknowledge the importance of innovation. In life science R&D firms scientists are crucial for innovation because they hold knowledge to create competitive new products. They are also known to fall outside of full control of management. Therefore, understanding the role of the CEO in innovation in life science R&D is key to understanding innovation in these firms. In order to gain insight into the role of the CEO a comprehensive review of the literature was conducted. It showed that the role of the CEO was mainly explored by means of survey-based investigations. The knowledge thus obtained has not offered insight into what CEOs actually do to lead innovation in life science R&D firms, nor does it take into account how it is perceived by R&D. It was therefore decided to conduct structured interviews of 15 CEOs of life science R&D firms to obtain a better understanding of what they actually do to lead innovation. Their views were contrasted against the perceptions of 33 R&D managers who report to the CEOs. It was found that CEOs need to make considerable use of their absorptive capacity to lead innovation and that they use this capacity to focus R&D. The R&D function refers to the need for the CEO’s absorptive capacity but emphasizes a relationship with the CEO based on trust. The unique contribution of this research is that not only takes into account the view of the CEO but also of the R&D function. For academics, it opens new avenues for research in innovation using CEO absorptive capacity. For practitioners, it advises CEOs to make efforts to improve their absorptive capacity in order to be able to lead innovation in life science R&D firms.